Effect of nanoparticles on the flow boiling heat transfer characteristics of refrigerant and performance of refrigeration systems: An experimental investigation - Sanukrishna S S; Maneesh Murukan; Reshmi Krishnan S (International Journal of Thermofluids)
The aim of the present work is to exploit the potential of nanoparticles in improving the heat transfer characteristics of refrigerant and to investigate the effect of nanorefrigerant in the overall performance of a vapour compression refrigeration system. Flow boiling heat transfer studies of R134a/Al2O3 nanorefrigerant have been conducted in a horizontal smooth tube at various mass fluxes, heat fluxes, particle concentrations, and vapour qualities. Furthermore, the coefficient of performance and power consumption of a refrigeration system is also evaluated. The results show that the flow boiling heat transfer coefficient of pure refrigerant has been increased substantially due to the presence of nanoparticles. The highest value of heat transfer coefficient observed was 197.4 W/m2 K at a particle concentration of 4 % and mass flux of 47 kg/m2s. Among the volume fractions considered, nanorefrigerant at volume fraction 0.4 % displays the maximum increase in heat transfer coefficient compared to pure refrigerant and the enhancement factor is found to be 80.54 %. The presence of nanoparticles in refrigerant penalties marginal increase in pressure drop. At lower concentrations (0.1 and 0.4 vol. %), refrigerant/nanolubricant mixture exhibits insignificant variation in pressure drop compared to pure refrigerant/lubricant mixture. However, an increase in pressure drop is displayed by nanolubricant at a particle dosing level of 0.8vol % particularly at higher vapour qualities. However, the recorded penalty in pressure drop is trivial compared to the enhanced heat transfer capability. The maximum pressure drop occurred was 25.42 kPa/m and is about 13.6 % higher compared to pure refrigerant.The performance test on a vapour compression refrigeration system witnessed a noteworthy diminution in the power consumption of the refrigerant compressor. The coefficient of performance of the refrigeration system with the use nanorefrigerants is increased by 7.5 % and the power consumption is reduced by 5.2 %. The studies show that the application of nanorefrigerants is an excellent energy-saving alternative to conventional refrigerants in refrigeration systems.